2012
DOI: 10.1002/aic.13979
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production by Sorption‐Enhanced Steam Glycerol Reforming: Sorption Kinetics and Reactor Simulation

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Sorption-enhanced glycerol reforming, an integrated process involving glycerol catalytic steam reforming and in situ CO 2 removal, offers a promising alternative for single-stage hydrogen production with high purity, reducing the abundant glycerol by-product streams. This work investigates this process in a fixed-bed reactor, via a two-scale, nonisothermal, unsteady-state model, highlighting the effect of key operating parameters on the process performance. CO 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…In the presence of CaO as the CO 2 sorbent, it was found that the in-situ CO 2 removal resulted in a significant enhancement of H 2 production and thermal efficiency as well as an important reduction of CO concentration [209,[217][218][219]. Chen et al [220] performed thermodynamic analyses on the SESGR process based on the principle of Gibbs free energy minimization for chemical reactions.…”
Section: Hydrogen Production By Sorption Enhanced Steam Glycerol Refomentioning
confidence: 98%
“…In the presence of CaO as the CO 2 sorbent, it was found that the in-situ CO 2 removal resulted in a significant enhancement of H 2 production and thermal efficiency as well as an important reduction of CO concentration [209,[217][218][219]. Chen et al [220] performed thermodynamic analyses on the SESGR process based on the principle of Gibbs free energy minimization for chemical reactions.…”
Section: Hydrogen Production By Sorption Enhanced Steam Glycerol Refomentioning
confidence: 98%
“…With the presence of steam in the gas mixture, MgO-based sorbents in the carbonation reaction could significantly increase the reactivity and capacity [73]. MgCO 3 can be formed in the presence of H 2 O due to the reactions of (4) and (5). And the used sorbent can be regenerated into Mg(OH) 2 (shown as (6)) at relatively low temperatures:…”
Section: Mgo Based Sorbentsmentioning
confidence: 99%
“…In addition, it is a low-cost hydrogen production due to reducing the number of processing steps required for subsequently separating CO 2 and decreasing the reaction temperatures for energy usage [1][2][3][4][5][6]. In general, SERP concept can be accomplished in different types of reactor configurations including (a) the interconnected fluidized-bed reactor; (b) alternating fixed-bed reactor; and (c) rotating reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This novel technology is normally called sorption-enhanced steam methane reforming (SESMR). Indeed, the concept of sorptionenhanced reaction process has recently also been applied to the steam reforming of ethanol and glycerol [11,12].…”
Section: Introductionmentioning
confidence: 99%